Nghiên cứu tổng hợp vật liệu xúc tác quang hóa Al/Al2O3/TiO2-Ag khả kiến ứng dụng để xử lý nước ô nhiễm - Thảo, Đỗ Thị; Thúy, Trần Thị; Tùng, Mai Thanh; Trường, Nguyễn Xuân (Vietnam Journal of Chemistry, 2014)
New visible light photocatalyst Al/Al2O3/TiO2-Ag is synthesized. The material is characterized using different analytical techniques such as X-ray diffraction (XRD), Energy Dispersive X-ray Spectroscopy (EDS), Diffusive Reflectance Spectroscopy (DRS) and Field Emission Scanning Electron Microscopy (FESEM). It is revealed that the Ag doped Al/Al2O3/TiO2 film drives the catalytic activity from UV to visible region. The environmental application of the photocatalyst is investigated by the degradation of methyl orange (MO) under sunlight. Furthermore, the effect of pH and H2O2 as an oxidizing agent on the degradation efficiency of the material is also studied. The results show the optimal conditions for the photodegradation of the MO 3mg sample are pH 2 and 1ml H2O2 9 % in 6-hour irradiation. Keywords: Visible light photocatalyst, photodegradation, methyl orange, environmental application, Ag doped Al/Al2O3/TiO2 film